Some nutritional properties of Taiwan Napier grass leaves (Pennisetum purpureum) harvested at different time - Malahubban, Masnindah; Abd Jalil, Nur Zahirah; Ab Aziz, Zakry Fitry; Kamaludeen, Juriah; Hassan, Mohammad Nasir; Saupi, Noorasmah (Update Publishing House, 2021)
The effect of different harvesting time on Napier grass's nutrient composition (Pennisetum purpureum) leaves was investigated. Taiwan Napier grass grown under field conditions were harvested at day-15, 30, 45, 60, 75, and 90 after planting. The leaves samples subjected for analyses on dry matter, moisture, ash, crude fibre, crude fat, crude protein and acid detergent fibre, and the data expressed as a percentage. The present study found that the different harvesting time had changed all nutrients composition, except, crude protein where no variation in crude protein during any harvesting time observed. The present study recommends harvesting time for Taiwan Napier grass between 45 and 60 days after planting was the best. This finding is useful as baseline data that provides information on Taiwan Napier's nutritional composition grown at a particular cropping site. It helps plan and strategy for new planting activity, especially when determining the best time for harvesting.